Evaluation of low-cost high performance solid-state supercapacitor derived from physically and chemically activated oil palm fiber - Tobi, A.R. (Elsevier B.V., 2021)
This study is geared towards harnessing the promises of Oil Palm Fiber (OPF) as a renewable substitute for electrode material of supercapacitor. Physical and chemical activation conversion methods were used to activate OPF. The structural and physiochemical properties of the activated carbon derived from OPF were studied and analyzed using FESEM, XRD, BET, XPS, and FTIR. The electrochemical properties of supercapacitors fabricated from POPF and COPF were studied and reported using cyclic voltammetry, Galvanostatic charge discharge and electrochemical impedance spectroscopy. Â© 2020 Elsevier B.V.